2009
DOI: 10.2527/jas.2007-0763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Biobullet versus traditional pharmaceutical injection techniques on injection-site tissue damage and tenderness in beef subprimals1

Abstract: The incidence and severity of injection-site lesions has decreased since the development of the Beef Quality Assurance program. The objective was to evaluate the route of administration and the pharmaceutical product on the impact on tenderness, collagen concentration, and lesion occurrence in muscles of chucks and rounds. A total of 144 yearling steers (initial BW = 383 ± 29.4 kg) were selected and transported to Oklahoma State University. Steers were blocked into 2 groups of 72 based on initial BW and were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In farm animal medicine, most research into injection techniques has been focused on improving meat quality by reducing tissue damage and tenderness complications created by injection‐site damage in prime cuts of meats. As muscles of the hindquarters are more valuable than cervical musculature, emphasis has been placed on training producers to use the neck region for all pharmaceutical products . Veterinary textbooks also recommend intramuscular injection in the neck region, and frequently caution that inappropriate injection technique or irritating medications in the hindquarters may cause sciatic nerve damage .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In farm animal medicine, most research into injection techniques has been focused on improving meat quality by reducing tissue damage and tenderness complications created by injection‐site damage in prime cuts of meats. As muscles of the hindquarters are more valuable than cervical musculature, emphasis has been placed on training producers to use the neck region for all pharmaceutical products . Veterinary textbooks also recommend intramuscular injection in the neck region, and frequently caution that inappropriate injection technique or irritating medications in the hindquarters may cause sciatic nerve damage .…”
mentioning
confidence: 99%
“…As muscles of the hindquarters are more valuable than cervical musculature, emphasis has been placed on training producers to use the neck region for all pharmaceutical products. 11 Veterinary textbooks also recommend intramuscular injection in the neck region, and frequently caution that inappropriate injection technique or irritating medications in the hindquarters may cause sciatic nerve damage. [12][13][14] For these reasons, many farm animal veterinarians are accustomed to cervical intramuscular injections, which are suitable for adult cattle, but in the authors' opinion contraindicated in camelids and small ruminants.…”
mentioning
confidence: 99%
“…In published studies, site and even route of administration, such as subcutaneously in the cervical area or in the ischio-rectal fossa (Chebel et al, 2007), did not affect efficacy of dinoprost in regression of the corpus luteum. Finally, the belief that reproductive hormones are less damaging to muscle tissue than vaccines, antimicrobial drugs, and anti-inflammatory drugs may be another reason for not using the neck for injection of reproductive hormones, although even injection of sterile water can cause lesions (Van Donkersgoed et al, 1999b;Sullivan et al, 2009). Because there are no published data on the formation of injection site lesions or impact on tenderness from use of reproductive hormones, determining the amount of muscle damage caused by injection of reproductive hormones in the hindquarters helps dairy producers and veterinarians to make more informed decisions about injection practices, balancing beef quality with human safety and convenience.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to changes in drug disposition, previous studies have shown that injections lead to damage to the injected area, with the resultant remodeling and fibrous infiltrate leading to changes in muscle tenderness ( George et al, 1996 ; George et al, 1995 ; Sullivan et al, 2009 ). Tenderness is an important contributor to consumer satisfaction of whole meat products such as steaks.…”
Section: Introductionmentioning
confidence: 99%